Large-area MoS2 grown using H2S as the sulphur source. (2nd November 2015) - Dumcenco, Dumitru; Ovchinnikov, Dmitry; Lopez Sanchez, Oriol; Gillet, Philippe; Alexander, Duncan T L; Lazar, Sorin; Radenovic, Aleksandra; Kis, Andras
Abstract: We report on the growth of molybdenum disulphide (MoS2 ) using H2 S as a gas-phase sulfur precursor that allows controlling the domain growth direction of domains in both vertical (perpendicular to the substrate plane) and horizontal (within the substrate plane), depending on the H2 S:H2 ratio in the reaction gas mixture and temperature at which they are introduced during growth. Optical and atomic force microscopy measurements on horizontal MoS2 demonstrate the formation of monolayer triangular-shape domains that merge into a continuous film. Scanning transmission electron microscopy of monolayer MoS2 shows a regular atomic structure with a hexagonal symmetry. Raman and photoluminescence spectra confirm the monolayer thickness of the material. Field-effect transistors fabricated on MoS2 domains that are transferred onto Si/SiO2 substrates show a mobility similar to previously reported exfoliated and chemical vapor deposition-grown materials.